Degradabilidade ruminal da matéria seca de grãos de milho e de sorgo com alto ou baixo conteúdo de tanino processados - Cação, Márcia Marise De Freitas; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP]; Galati, Rosemary Lais; Silva, Marina Gabriela Berchiol da [UNESP] (UFBA - Universidade Federal da Bahia, 2012)
This work evaluated the effects of high moisture silage, extrusion and corn and sorghum drying with and without tannin, on the chemical composition and ruminal digestion of dry matter. The experimental design was completely randomized in 3x3 factorial scheme (kinds of grains: processing), for the chemical composition and degradability and three blocks (animals) through in situ method. It was verified significant difference between kinds of grains and processing in relation to the chemical composition, except for crude protein and mineral matter. The contents of etherextract in the three types of grains, were reduced significantly with the high moisture silage, extrusion and drying in relation to the humid material. For the contents of phenols, total and condensed tannin there was effect of hybrid, processing and interaction, and the most elevated contents were found in sorghum with tannin. Although grain composition has been similar, the interaction in ruminal ambient associated to the tannin, promoted differences in the dry matter degradability. It was concluded that sorghum without tannin may be ensiled or extruded, while the sorghum with tannin, must be extruded to improve the degradability and availability of nutrients.

Avaliaram-se os efeitos da ensilagem, extrusão e secagem do milho e sorgo com alto e baixo conteúdo de tanino sobre a composição química e a degradação ruminal da matéria seca. O delineamento experimental foi inteiramente casualizado, em esquema fatorial 3x3, (tipos de grãos x processamentos) para a composição química e degradabilidade com três blocos (animais) pelo método in situ. Quanto à composição química, com exceção da proteína bruta e matéria mineral, constatou-se diferença significativa entre os tipos de grãos e processamentos. Os teores de extrato etéreo nos três tipos de grãos foram reduzidos significativamente com a ensilagem, extrusão e secagem em relação ao material úmido. Nos teores de fenóis, tanino total e condensado, houve efeito do híbrido, do processamento e da interação e, no sorgo com alto conteúdo de tanino, os teores mais elevados. Embora a composição dos grãos tenha sido similar, a interação no ambiente ruminal, associada ao tanino, proporcionou diferenças na degradabilidade da matéria seca. Concluiu-se que o sorgo com baixo conteúdo de tanino pode ser ensilado ou extrusado, enquanto o sorgo com alto conteúdo de tanino, deve ser extrusado, para melhorar a degradabilidade e a disponibilidade de nutrientes no rúmen.
Ruminal dry matter degradability of corn and sorghum grains at high or low tannin contents submitted to processing
Keywords: extrusão; fenóis totais; grãos secos; silagem de grão úmido; dry grains; extrusion; high moisture silage of grain; total phenols